THE IMPORTANCE OF MODERN WORK ETIQUETTE (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
Any work has rules of communication — work etiquette. We tell you why you need it and what principles you need to follow in order to keep your job and good relationships with colleagues. Work etiquette is a set of rules on which employees communicate with each other, as well as with managers, clients and partners.